Electronically Switchable Broadband Metamaterial Absorber - Dongju Lee (Nature Portfolio, 2017)
Abstract In this study, the novel electronically switchable broadband metamaterial absorber, using a PIN diode, is proposed. The unit cell of the absorber was designed with a Jerusalem-cross resonator and an additive ring structure, based on the FR-4 dielectric substrate. Chip resistors and PIN diodes were used to provide both a broadband characteristic and a switching capability. To satisfy the polarization insensitivity, the unit cell was designed as a symmetrical structure, including the DC bias network, electronic devices, and conductor patterns. The performance of the proposed absorber was verified using full-wave simulation and measurements. When the PIN diode was in the ON state, the proposed absorber had a 90% absorption bandwidth from 8.45–9.3 GHz. Moreover, when the PIN diode was in the OFF state, the 90% absorption bandwidth was 9.2–10.45 GHz. Therefore, the absorption band was successfully switched between the low-frequency band and the high-frequency band as the PIN diode was switched between the ON and OFF states. Furthermore, the unit cell of the proposed absorber was designed as a symmetrical structure, and its performance showed insensitivity with respect to the polarization angle.